Clinical study of neurology nursing on cerebral apoplexy rehabilitation - Chen Jie (De Gruyter, 2019)
The incidence of cerebral apoplexy has been on the rise in recent years, and research on the treatment and care of this disease has also received much attention. Therefore, a clinical study of neurological care for cerebral apoplexy rehabilitation care was conducted. Firstly, the Diffie-Hellman key exchange algorithm is introduced, and then the Diffie-Hellman prediction model is established. The patient is taken as an example to carry out simulation test, and the prediction model is compared with the real data. The data of the network model training set, the verification set and the test set are obtained. Patients were divided into observation group and control group by random number table method. The evaluation indicators included the treatment efficiency and the quality of life of the two groups. The results showed that the effective rate of the observation group was higher than that of the control group, and the difference between the two groups was statistically significant (P < 0.05). The experiment proves that the clinical effect of neurological nursing on cerebral apoplexy rehabilitation nursing is positive, which can improve the limb movement and self-living ability of patients, improve the quality of life of patients and improve patient satisfaction. Clinical study of neurology nursing on cerebral apoplexy rehabilitation nursing is discussed in this paper, and the rehabilitation nursing method and formal standardized nursing process of this disease are standardized.